Content Mastery Services to Improve Student Article Publication Capability: An Action Research - Abdurrahman Abdurrahman; Annisa Arrumaisyah Daulay; Muhammad Putra Dinata Saragi; Helsa Nasution; Adinda Azzahra (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Content services to improve student article publishing ability an action research. Many universities have started to encourage their students to write and publish scientific articles. However, the lack of knowledge and understanding of students in writing and publishing scientific articles makes it difficult for them to fulfill assignments or choose completion of studies through the article route for final students. The purpose of this study was to describe and analyze students' understanding of writing and publishing scientific articles before and after being provided with content mastery services. This type of research is action research (action research). The research approach is quantitative and qualitative. The subjects were students of UINSU with a total of 27 people who were selected using purposive sampling technique. The data collection technique used an understanding instrument for writing scientific articles and methods of interview, observation, and documentation study. Data were analyzed with validity, reliability, normality test, and paired sample t test. Based on the results, it shows that the implementation of the content mastery service 'scientific article writing class' has a significant effect on increasing students' understanding and ability to write and publish scientific articles.